A case of G1013R FBN1 mutation: A potential genotype–phenotype correlation in severe Marfan syndrome. Issue 6 (21st March 2020) - Willis, Brooke R.; Lee, Mianne; Rethanavelu, Kavitha; Fung, Jasmine L. F.; Wong, Rosanna M. S.; Hui, Peter; Yeung, Kit S.; Lo, Ivan F. M.; Chung, Brian H. Y.
Abstract: Marfan Syndrome (MFS) is an autosomal dominant connective tissue disorder with a wide range of severities. Ninety‐five percent of MFS probands have a mutation in the fibrillin‐1 gene ( FBN1 ); however, there are a high number of unique mutations complicating attempts at establishing any phenotype–genotype correlations for this disease (Tiecke et al., European Journal of Human Genetics, 2001, 9, 13–21). One of the few extant genotype–phenotype correlations is in exon 24–32 which have been associated with a severe pediatric presentation of neonatal MFS with predominately cardiovascular symptoms. We present a 24‐year‐old male patient with a heterozygous de novo variant NM_000138.4: c.3037G>A (p.G1013R) located in exon 25 of the FBN1 gene. The patient was found to have dysplastic mitral and tricuspid valves with dilated aortic root at 9 months of age. This is a notable case in that the location of this patient's mutation and his age of symptom onset would indicate a guarded prognosis. Further, this mutation, FBN1 G1013R, has been reported in the literature in four other unrelated patients all of whom presented at a young age with cardiac involvement and all of whom had relative longevity when compared to other patients with mutations in this exon 24–32 hot spot. These findings may represent a more specific genotype–phenotype correlation within this mutational hot spot.